Remission of OCD and ulcerative colitis with a ketogenic diet: Case Report - Calabrese, Lori (Frontiers in Psychiatry, 2025)
BackgroundThere is little research describing the clinical use of a ketogenic diet in obsessive-compulsive disorder (OCD) or inflammatory bowel disease. We describe the first clinical application of a ketogenic diet in adult OCD with ulcerative colitis (UC) resulting in complete remission of OCD, clinical remission of UC, and improved metabolic health.MethodsA 37-year-old obese woman with longstanding OCD and ulcerative colitis was treated for 12 weeks with a personalized whole-food ketogenic diet (KMT 1:5:1 ratio) in a specialized metabolic psychiatry clinic. Adherence was assessed by capillary beta-hydroxybutyrate (BHB) and photojournaling of food intake. Remission of OCD was assessed by the Yale-Brown Obsessive Compulsive Scale (Y-BOCS), Florida Obsessive Compulsive Inventory scale (FOCI), and Clinical Global Impression-Improvement/Severity scale (CGI-S/I). Patient Health Questionnaire-9 (PHQ-9) and Yale Food Addictions Scale 2.0 (YFAS 2.0) assessed depression and food addiction. Remission of UC was assessed by the Partial Mayo Score (PMS) and the Ulcerative Colitis Patient-Reported Outcome (UC-PRO). Metabolic health was assessed by laboratories and bioimpedance. Quality of life was assessed using validated scales for flourishing, resilience, self-compassion, and subjective narrative.ResultsClinical remission of UC occurred within 3 weeks (PMS 0, UC-PRO 0). Progressive improvement in OCD was inversely related to oscillating BHB, with FOCI 0 at 9 weeks, and complete remission at 12 weeks (Y-BOCS 0, CGI-S 1). Body weight decreased 12.2%, with significant decreases in the percentage of body fat and visceral fat. Flourishing, resilience, and self-compassion improved 2- to 20-fold.ConclusionComplete remission of OCD, clinical remission of UC, and marked improvement in metabolic health occurred within 12 weeks using a well-formulated personalized ketogenic diet (KMT ratio 1:5:1) with a meaningful positive impact on quality of life and significant improvements in flourishing, resilience, and self-compassion.